The analyses of the reinforced concrete beam sections by artificial neural networks - Keleşo?lu, Ömer (My University, 2006)
The inspirations of the artificial neural networks are the sensitivity, elasticity and power of the biological brain. Artificial neural network is the mathematical model of the dendrite and the synopsis and the nerve cells from the basic biological components of the brain and is composed of simple mathematical components. In this study, the analyses of the reinforced concrete beam sections have been examined. In numerical applications, fix-end beam and T-beam sections have been used and reinforcement steel area and bearing capacity moment and design moment of the sections have been analyzed. A backpropagation neural network for artificial neural network has been preferred and the data have been presented to network by being normalized. The results obtained have been compared with numerical results and it was seen that artificial neural networks could be an alternative method for the analyses of the engineering systems.
Yapay sinir a?lari ile betonarme kiriş kesitlerin analizi
Keywords: Artificial neural network; Backpropagation neural network; Bearing capacity moment; Design moment; Reinforced concrete beam section